2014
DOI: 10.1097/prs.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

Breast Reconstruction Using Free Posterior Medial Thigh Perforator Flaps

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 19 publications
2
55
0
3
Order By: Relevance
“…Recently, Satake et al reported the free posterior medial thigh perforator flap for breast reconstruction in women with a small to moderate breast size. 18 Inspired by their innovative work, the authors modified the flap design without including the skin of the posterior thigh below the gluteal fold and subsequently applied it to head and neck reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Satake et al reported the free posterior medial thigh perforator flap for breast reconstruction in women with a small to moderate breast size. 18 Inspired by their innovative work, the authors modified the flap design without including the skin of the posterior thigh below the gluteal fold and subsequently applied it to head and neck reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Allen et al reported the profunda artery perforator flap for autologous breast reconstruction when abdominal tissue was not available and, recently, the posterior medial thigh flap has been described as a free flap for breast reconstruction. [16][17][18] To our knowledge, there is a paucity of data describing the clinical application of this flap for head and neck reconstruction. In this article, we report our experience in using the posteromedial thigh flap for head and neck reconstruction and describe the perforator patterns, flap design, and dissection technique; we also discuss its clinical indications and the advantages and versatility of this flap compared with the conventional lower extremity perforator flaps.…”
mentioning
confidence: 96%
“…Dans les travaux fondateurs d'Allen et al [9] et Satake et al [10], le prélèvement du lambeau se faisait soit en décubitus ventral, soit en décubitus dorsal le membre inférieur en grenouille (cuisse en abduction et genou fléchi). Dans notre étude, nous avons opté pour la position gynécologique modifiée [11,12] qui offre les avantages des deux positions sans leurs inconvénients.…”
Section: Discussionunclassified
“…Dans notre série, le poids moyen du lambeau PAP classique était de 234,4 g. Dans la série d'Allen et al [9], ce poids moyen était de 385 g. Dans la série de Satake et al [10], le poids moyen était de 199,8 g en cas de reconstruction immédiate, et 244,6 g en cas de reconstruction secondaire. Pour les cinq patients ou l'extension verticale a été réalisée, le poids moyen était de 461 g, soit une augmentation moyenne de 226,6 g, permettant d'élargir les indications du lambeau aux seins de plus grand volume.…”
Section: Discussionunclassified
See 1 more Smart Citation